PARADIGMA PENELITIAN KOMUNIKASI - Effendi, Muchtar (Fakultas Dakwah IAIN Purwokerto, 2007)
Current researches tend to accommodate environment factors and are often dominantly influenced by them. This is a reasonable condition since the nature of communication Science is a contextual one so that it cannot be separated from the facts in its surroundings. The discussion on the development and trends in communication Science will be more interesting to study because in the present time there are many methods and analysis which are applied to understand the elements of communication Science. In accordance to this fact, it is expected that in the near future, communication Science will be more developed and has more complete fields of study in order to give more benefits to society.